DNA methylation of a non-CpG island promoter represses NQO1 expression in rat arsenic-transformed lung epithelial cells. (8th June 2018) - Huang, Ningyu; Pei, Xiaojuan; Lin, Wenbo; Chiu, Jen-Fu; Tao, Tao; Li, Guanwu
Abstract: NAD(P)H:quinone oxidoreductase 1 (NQO1), a phase II flavoenzyme that catalyzes reduction reactions to protect cells against electrophiles and oxidants, is involved in tumorigenesis. Altered methylation of the NQO1 gene has been observed and is speculated to result in aberrant NQO1 expression in rat cells undergoing chemical carcinogenesis, although this has not been proven experimentally. In this study, we first investigated the potential epigenetic mechanisms underlying the phenomenon of NQO1 differential expression in individual subclones of rat arsenic-transformed lung epithelial cells (TLECs). NQO1 expression of TLEC subclones with or without 5-aza-2′-deoxycytidine (5-Aza-CdR) treatment was assessed by reverse transcriptase-polymerase chain reaction (RT-PCR), western blot analysis, and real-time PCR. Methylation status of the NQO1 promoter in TLEC subclones was analyzed by bisulfite sequencing. Transcriptional activity of NQO1 promoter in vitro methylated was determined by luciferase assay using a CpG-free luciferase reporter driven by the NQO1 promoter region (−435 to +229). We found that non-CpG island (non-CpGI) within the NQO1 promoter was hyper- or hypo-methylated in TLEC subclones and corresponded to low and high gene expressions, respectively. Following the treatment with 5-Aza-CdR, transcription of the NQO1 gene in the hypermethylated subclones was restored, accompanied by demethylation of the NQO1 promoter. In vitro promoter methylation almost completely silenced reporter activity in TLECs. These results indicate that DNA methylation of the non-CpGI promoter contributes to epigenetic silencing of NQO1 in rat TLECs.